2011
DOI: 10.1111/j.1467-8659.2011.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Correspondence Construction Using Manifold Learning

Abstract: Stroke correspondence construction is a precondition for generating inbetween frames from a set of key frames. In our case, each stroke in a key frame is a vector represented as a Disk B-Spline Curve (DBSC) which is a flexible and compact vector format. However, it is not easy to construct correspondences between multiple DBSC strokes effectively because of the following points: (1) with the use of shape descriptors, the dimensionality of the feature space is high; (2) the number of strokes in different key fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Here, the single‐point energy calculations are based on the B3LYP/6‐311+G(2d,2p) and MP2/6‐311G(d,p) optimized geometries, respectively. It has been shown that in many studies 17–21 this method can provide reliable PES information. Original G3(MP2) calculations are also performed for comparison.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Here, the single‐point energy calculations are based on the B3LYP/6‐311+G(2d,2p) and MP2/6‐311G(d,p) optimized geometries, respectively. It has been shown that in many studies 17–21 this method can provide reliable PES information. Original G3(MP2) calculations are also performed for comparison.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Early stroke-based approaches [Burtnyk and Wein 1971;Reeves 1981;Fekete et al 1995] are manual (the animator selects pairs of strokes to interpolate) and topology-unaware (strokes are interpolated independently, unaware of their neighbors). Recent methods [Liu et al 2011;Yu et al 2012] use shape descriptors and machine learning techniques to compute stroke correspondences automatically, but since they are topologyunaware, they are unable to generate space-time continuous animation with time-varying topology.…”
Section: Introductionmentioning
confidence: 99%
“…In [LCY*11, YBS*12], a stroke reconstruction algorithm is proposed to resolve the topology ambiguities. However, such algorithm often fails in practice, since it is akin to a difficult artificial intelligence problem to infer the occluded parts from the key drawings or to associate the stroke(s) that correspond to a common feature between the successive key frames.…”
Section: Introductionmentioning
confidence: 99%